High-frequency controls on alluvial successions: An integrated sedimentological and palaeopedological approach to the Plio- Pleistocene of Argentina - Beilinson, Elisa (2013)
Plio-Pleistocene palaeosol-bearing alluvial strata are continuously exposed along the marine cliffs of southeastern Buenos Aires province, Argentina. The study interval was deposited by a mixed, predominantly suspended-load fluvial system. Outcrops are dominated by floodplain siltstones and mudstones that exhibit a cyclic alternation between calcic and vertic palaeosols. This cyclicity is represented by meter-scale alluvial cycles that show as a general trend a gradual increase in the proportion of channel-fill deposits up-section. Cyclic variations in palaeosols, facies and architectural elements can be related to allogenic drivers such as climate and eustasy. For the lower Punta San Andrés Alloformation, the stratigraphic arrangement of the recognised palaeosols and the clay mineral distribution indicate that the palaeoclimate was subhumid (average mean annual precipitation [MAP] ∼840 mm), seasonal and temperate (average mean annual temperature [MAT] ∼7.85 °C) for at least 1 Ma, from ca. 2.9 Ma to ca. 1.8 Ma (late Pliocene–early Pleistocene), with several intervals in which conditions became drier and probably colder. Even though climate was a major control on palaeosol development, it is suggested here that it was not the main control on high-frequency cycles. Variations in the orbital parameters, more specifically in insolation, were interpreted as having controlled the sedimentation and architectural evolution of the lower Punta San Andrés Alloformation depositional systems.